Irregularity in Plantar Fascia, Muscle Edema and Tendon Thickness in Patients with High-Risk for Diabetic Foot - Korkmaz, Busra Yurumez; Akturk, Mujde; Ucar, Murat; Altınova, Alev Eroglu; Can, Mehmet Ali; Arslan, Emre; Tokgoz, Nil; Toruner, Fusun (Experimental and Clinical Endocrinology & Diabetes, 2021)
Aim To investigate the alterations in the plantar fascia (PF), intrinsic muscles, and tendons in the feet of patients at high risk for developing diabetic foot.Methods The healthy feet of 22 patients with type 2 diabetes, who had developed diabetic foot ulcers on a single foot without any pathology on the contralateral extremity, and those of 22 healthy volunteers were evaluated by magnetic resonance imaging. The volume of the Achilles tendon (AT), the surface area of the PF, the thickness of AT, flexor hallucis longus, flexor digitorum longus, tibialis posterior, and peroneus longus tendons, irregularity in the PF, and edema of intrinsic foot muscles were examined.Results Nineteen patients (86%) had irregularity in the PF, whereas none of the healthy controls had any (p<0.001). Intrinsic muscle edema was more common in the group with diabetes (p=0.006). The volume of AT and the surface area of PF were decreased in patients with peripheral arterial disease (PAD) (p<0.05). Patients with diabetes mellitus but without PAD had a larger surface area of PF than that of controls (p<0.05). There were no differences in the volume of AT, the surface area of the PF, and other tendon thickness between the groups.Conclusion Irregularity in the PF and muscle edema may indicate a high risk for the diabetic foot. The presence of PAD may lead to regression in the structure of AT and PF.
Keywords: diabetes mellitus; tendon; Achilles; MRI; peripheral arterial disease